Une hétérogénéité déconcertante : peut-on encore définir le nom propre ? - Jean-Louis Vaxelaire (Corela)
According to traditional grammar, the question regarding proper nouns is simple: they can be separated into personal names and place names, an additional category is sometimes added, and they are opposed to common nouns on a certain number of criteria (absence of a determiner, the initial is written with a capital letter, etc.). However, as soon as we are confronted with authentic corpora, this simplicity is shattered: the category of proper nouns is much more heterogeneous than we usually think it is and the criteria generally used to define them sometimes become obsolete. We will try to classify the series of terms that have been proposed for analysis, either as proper nouns or as common nouns, with the help of the notion of norms and the linguistic context, as a new definition, different from the one that can be found in grammars, is necessary.